Characterization of Neonatal Seizures in a Large Well-defined Multicenter Cohort of a Tertiary Neonatology Center in Germany - Kraus, Verena; Schatz, Ulrich; Krüger, Marcus; Krampe-Heni, Franziska (Neuropediatrics, 2025)
Prevalence of seizures is 1 to 5/1,000 neonates. The most common causes of neonatal seizures are hypoxic–ischemic encephalopathy (HIE), vascular events (hemorrhages, stroke), and infections. We assessed prevalence and etiology of seizures defined according to the recent Brighton and International League of Epilepsy (ILAE) criteria in a neonatology monocenter cohort.In a retrospective cross-sectional cohort study of all 12,154 neonates born in our three maternities from January 1, 2022 to December 31, 2023 seizures were categorized by frequency, etiology, risk profile, semiology, and EEG. A total of 19 neonates (male: n = 11 [57.9%]; full-term: n = 11 [57.9%]; preterm very low birth weight [VLBW]: n = 6 [31.6%]; preterm >1,500 g birth weight: n = 2 [10.5%]) were identified.In 19/12,154 neonates, seizures were confirmed by application of the ILAE criteria. Preterm VLBW was found in 174 neonates with birth weight <1,500 g. Seizure incidence was 1.6/1,000 in all neonates and 3.4% in VLBW infants. HIE was the most frequent etiology in term infants (30.8%), followed by vascular events in preterm >1,500 g and term infants (30.8%). Vascular events were the most common cause in preterm VLBW infants (83.3%). Whole exome sequencing (WES) was performed in four cases (21.1% of neonates with seizures).Incidence of neonatal seizures in our center is in the lower range and leading seizure etiologies are comparable to the literature. Early recognition of neonatal seizures including the detection of electrographic-only seizures and early WES to identify rare genetic defects possibly offering tailored treatment options have the potential to further raise the standard of neonatal care and improve neurodevelopmental outcome.
Keywords: neonatal seizures; seizures; perinatal care